2020
DOI: 10.1177/0896860820966898
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis access outcomes reported in randomized controlled trials: A systematic review

Abstract: Background: Functional peritoneal dialysis (PD) access is critical to the success of PD therapy. The aim of this review is to describe the spectrum of definitions and methods employed in the measurement of unique outcomes across PD access trials particularly focusing on the outcomes of PD access flow restriction and operative-related outcomes. Methods: Using Cochrane CENTRAL registry, MEDLINE, and EMBASE, we searched for studies restricted to randomized controlled trials (RCTs) involving interventions related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…To enable comparisons across future studies, we have adopted the recently proposed definitions. 3 Entry point for time on PD therapy is taken from first day of PD training. For those who converted to HD, the first day of HD is taken as the exit point.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To enable comparisons across future studies, we have adopted the recently proposed definitions. 3 Entry point for time on PD therapy is taken from first day of PD training. For those who converted to HD, the first day of HD is taken as the exit point.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no previous studies have reported comparisons of the two techniques using the proposed standardized outcomes. 3 Future studies need to use standardized definitions to enable comparisons across jurisdictions and to allow identification of potentially modifiable risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of PD technique failure are due to mechanical catheter complications (4)(5)(6). Additionally, there is in the definitions, reporting methods, choice of outcomes, and analysis of PD access outcomes which hampers the determination of best practices for PD catheter placement (7).…”
mentioning
confidence: 99%